Sore Throat in Children - O.Ye. Chernysheva; B.I. Krivuschev; Yu.A. Soroka (Zaslavsky O.Yu., 2012)
There were considered causes of sore throat, approaches to the diagnosis of various diseases of the mouth and throat, associated with pain syndrome, treatment.